Impact of severe chronic periodontitis on oral health-related quality of life - Sulaiman, Leilawati; Saub, Roslan; Baharuddin, Nor Adinar; Safii, Syarida Hasnur; Krishna, Vignes Gopal; Bartold, P. Mark; Vaithilingam, Rathna Devi (Quintessence Publishing, 2019)
Purpose: To assess the impact of extent and severity of chronic periodontitis (CP) on oral health-related quality of life (OHRQoL). Materials and Methods: A cross-sectional comparative study was performed on subjects from multiple dental centres in Malaysia using a questionnaire covering sociodemographics, OHRQoL using the Malaysian Oral Health Impact Profile questionnaire, OHIP-14(M) and self-reported symptoms. Participants with severe CP were age-and gender-matched with periodontally healthy/mild periodontitis (HMP) participants based on inclusion and exclusion criteria. Full mouth periodontal examination was performed on participants. Outcome measures were OHIP-14(M) prevalence of impact and severity of impact scores. Results: One hundred and thirty (130) participants comprising 65 severe CP and 65 HMP participants were included in the study. Prevalence of impact on OHRQoL was significantly higher in the severe CP than HMP group, with an odds ratio of 3. Mean OHIP-14(M) score was significantly higher in the severe CP (18.26 ± 10.22) compared to HMP (11.28± 8.09) group. The dimensions of psychological discomfort and functional limitation, and factors such as 'discomfort due to food stuck' and 'felt shy' were impacted more in severe CP compared to HMP group (p < 0.05). When compared with the HMP group, generalised severe CP participants showed higher prevalence of impact on OHRQoL [OR=5] (p < 0.05) compared to localised severe CP [OR=2] (p = 0.05). Participants who had experienced self-reported symptoms had statistically significant impacts on OHRQoL. Conclusions: Severe CP had a greater impact on OHRQoL compared to HMP. Impacts were mainly for functional limitation and psychological discomfort dimensions. When considering extent of disease, the impact on OHRQoL was mostly in generalised severe CP subgroup. © Quintessenz.